Performance Evaluation of Wireless LAN for UAS Communication - Kim, Tae Yoon; Cho, Jun Woo; Kim, Jae Hyun (International Conference on Information Networking, 2021)
One of the most important things in the unmanned aerial systems (UAS) operation using drones is wireless communication. Ground control station (GCS), which is part of UAS, periodically receives a drone status or transmits the mission to a drone via a stable wireless communication system. For the connection between the GCS and the drone, wireless local access networks (WLANs) are commonly used based on Wi-Fi. However, since Wi-Fi uses the industrial-science-medical (ISM) band, WiFi-based UAS results in performance degradation due to signal interference. In this paper, we first analyze the performance of the IEEE 802.11 protocols such as 802.11 b/g/n for the wireless communication of UAS. Using the UAS model, we measure the video transmission time and the round trip time (RTT) using SockPerf to compare each 802.11 protocol's performance. Besides, we analyze the effect of signal interference by changing the frequency band.
Keywords: Ground control stations; IEEE 802.11 protocols; Performance degradation; Unmanned aerial systems; Video transmissions; Wireless communication system; Wireless communications; Wireless local access networks; 802.11 standard; drone; UAS; Wi-Fi; WLAN